THE EFFECT OF CALCIUM STEARATE USAGE IN SELF COMPACTING CONCRETE 20 MPA WITH PCC AND FLY ASH AS BINDERS TOWARD ON PULL OUT CAPACITY OF REINFORCEMENT - Maryoto, Agus; Maulana, Ikhsan; Hermanto, Nor Intang Setyo (Universitas Ibn Khaldun Bogor, 2022)
Concrete is widely used for buildings because of its high compressive strength. Reinforced concrete must be able to withstand water infiltration into the concrete. This is to prevent the infiltration of corrosive ions with water that cause corrosion attacks on the reinforcement. One type of concrete that can reduce the infiltration of water into the concrete is Self Compacting Concrete (SCC). SCC generally uses a very small water cement ratio, so it can reduce water infiltration into the concrete. SCC is not enough to cover with corrosion attack significantly. The use of added calcium stearate has been shown to significantly reduce corrosion attack on concrete reinforcement. Unfortunately, the effect of calcium stearate usage on the bond strength of reinforcement and concrete has not been well studied. This study aims to determine the effect of calcium stearate on 20 MPa concrete with doses of 0, 1, 5 and 10 kg/m3 on the pull out capcity and failure pattern of the concrete. The tests carried out include the compressive strength test and the pull out capacity. The results showed that the average pull out capacity with the addition of calcium stearate 0, 1, 5, and 10 kg/m3 were 5.78, 4.08, 3.83, and 3.45 MPa, respectively. The type of failure that occurs when the maximum load is reached is a splitting failure.